Corn and Velvetleaf (Abutilon theophrasti) Growth and Transpiration Efficiency under Varying Water Supply. Issue 4 (December 2016) - Vaughn, Logan G.; Bernards, Mark L.; Arkebauer, Timothy J.; Lindquist, John L.
Abstract : The supply of soil resources is critical for the establishment and long-term competitive success of a plant species. Although there is considerable research on the effects of water supply on crop growth and productivity, there is little published research on the comparative response of crops and weeds to limiting soil water supply. The objective of this research was to determine the growth and transpiration efficiency of corn and velvetleaf at three levels of water supply. One corn or velvetleaf plant was grown in a large pot lined with plastic bags. When seedlings reached 10 cm, bags were sealed around the base of the plant, so the only water loss was from transpiration. Daily transpiration was measured by weighing the pots at the same time each day. The experiment was conducted in the fall of 2007 and in the spring of 2008. Four replicates of each species–water treatment were harvested periodically to determine biomass accumulation and leaf area. The relationship between cumulative aboveground biomass and water transpired was described using a linear function in which the slope defined the transpiration efficiency (TE). Corn TE was greater than velvetleaf TE in all treatments during both trials. In the fall trial, corn TE was 6.3 g kg –1, 47% greater than that of velvetleaf TE. In the spring trial, TEs of both species were lower overall, and corn TE increased with declining water supply. Corn produced more biomass and leaf area than velvetleaf did at all water-supply levels. Velvetleaf partitioned more biomass to roots compared with shoots during early growth than corn did. The ability of corn to generate more leaf area and its investment in a greater proportion of biomass into root growth at all levels of water supply may enable it to more-effectively avoid velvetleaf interference under all levels of soil-water supply.